Using accelerometry to quantify prey attack and handling behaviours in piscivorous pike Esox lucius. Issue 6 (9th April 2017) - Van Deurs, M.; Andersson, A.; Vinterstare, J.; Didenko, A.; Persson, A.; Brönmark, C.; Nilsson, P. A.
Abstract : Accelerometer technology was used to evaluate behaviours in the teleost ambush predator pike Esox lucius foraging on crucian carp Carassius carassius . Automated rule‐based estimates of prey‐size determined handling time were obtained and are compared with video‐recorded behaviours. Solutions to tag attachment and the limitations imposed by battery‐time and data‐logging capacities are evaluated.